2021
DOI: 10.48550/arxiv.2107.09530
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Into the Storm: Diving into the winds of the ultra hot Jupiter WASP-76 b with HARPS and ESPRESSO

J. V. Seidel,
D. Ehrenreich,
A. Allart
et al.

Abstract: Context. Despite swift progress in the characterisation of exoplanet atmospheres in composition and structure, the study of atmospheric dynamics has not progressed at the same speed. While theoretical models have been developed to describe the lower layers of the atmosphere and, disconnected, the exosphere, little is known about the intermediate layers up to the thermosphere. Aims. We aim to provide a clearer picture of atmospheric dynamics for the class of ultra hot Jupiters, highly-irradiated gas giants, on … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 67 publications
(138 reference statements)
0
14
0
Order By: Relevance
“…We emphasize that, despite the high number of species we detected in HAT-P- 70 b and the remarkable strength of some of them (e.g. Fe II), the work presented here only used a single transit event with HARPS-N -further studies could reveal additional species and allow for a detailed investigation of the atmospheric dynamics of HAT-P-70 b (Wardenier et al 2021;Seidel et al 2021). HAT-P-70 b is also a promising target for emission spectroscopy to investigate the chemistry of its day-side (e.g.…”
Section: Detection Of Hα Hβ and Hγmentioning
confidence: 95%
“…We emphasize that, despite the high number of species we detected in HAT-P- 70 b and the remarkable strength of some of them (e.g. Fe II), the work presented here only used a single transit event with HARPS-N -further studies could reveal additional species and allow for a detailed investigation of the atmospheric dynamics of HAT-P-70 b (Wardenier et al 2021;Seidel et al 2021). HAT-P-70 b is also a promising target for emission spectroscopy to investigate the chemistry of its day-side (e.g.…”
Section: Detection Of Hα Hβ and Hγmentioning
confidence: 95%
“…We chose to use an isothermal PT profile with a temperature of 3000 K. An isothermal PT profile is often used for transmission spectroscopy as this type of spectrum is not very dependent on the underlying PT profile. Indeed, Seidel et al (2021) found that an isothermal profile fit this ESPRESSO data well and was preferred over the more complex profiles that they tested. A temperature of 3000 K was motivated as an intermediate choice between Landman et al (2021), who retrieved a best-fit temperature of 2701 +448 −279 , and Seidel et al (2021), who found a best-fit temperature of 3389 ± 227 K. Figure 2 shows how changing the temperature changes the resulting model spectrum, and in Section 6.1 we test how our results change if we use isothermal PT profiles of 2000 and 4000 K.…”
Section: Atmospheric Transmission Modelsmentioning
confidence: 95%
“…More information about the reduction procedure and the data can be found in the original publication where the data were presented (Ehrenreich et al 2020). This dataset has also been used in two subsequent papers, Tabernero et al (2021) and Seidel et al (2021). Tabernero et al (2021) identified individual absorption lines from Li I, Na I, Mg I, Ca II, Mn I, K I, and Fe I, and also searched for Fe I, Ti I, Cr I, Ni I, TiO, VO and ZrO using the cross correlation technique, but only detected the previously-seen Fe I signal.…”
Section: The Datamentioning
confidence: 99%
See 2 more Smart Citations